Understanding factors that influence whether a woman will seek care for reproductive health: A national survey - Pooja Kanyadan; Latha Ganti; Rohan Mangal; Thor Stead; Lindsey Hahn; Marcos Sosa (Health Psychology Research)
A number of studies have characterized the importance of regular OB/GYN visits for women who are above the age of 18. As more emphasis is placed on reproductive healthcare, there has been an overall decrease in the rates of adverse sexual and reproductive health outcomes. In this study, a population of 200 women were surveyed to find factors that influence whether they had sought care from an OB/GYN in the past year. These results can be further extrapolated to whether women will seek OB/GYN healthcare in the future. A survey research platform was used to collect demographic data in addition to the survey responses. Thirteen survey questions were designed, some of which were adapted from the NIH Healthcare Access and Utilization Survey. This study found that women of minority races (African American and Hispanic) were more likely to report that they didn’t feel like they were asked for their opinions about their healthcare. Additionally, women who were younger, who didn't feel like they were asked for their opinions, and who were of minority races were more likely to have not seen an OB/GYN in the past year. These findings can be used to focus on fixing the factors that deter women from seeking regular OB/GYN care. Efforts must be made to ensure that patients feel supported and understood, for this is the only way that we can make progress towards a healthier society.